(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Based on the balanced scorecard, starting from the IT strategic goal of digital transformation, this paper deconstructs the strategic goal into four dimensions: “finance”, “customer”, “internal process”, and “learning and growth”. According to the characteristics of textile and garment enterprises, this paper puts forward the performance evaluation index system for the digital transformation of textile and garment enterprises. Using this evaluation index system, we collected data from 201 textile and garment enterprises by questionnaire and evaluated their digital transformation performance. The results show that all effective sample enterprises have performed well on the first-level performance indicators of digital transformation. However, variance analysis shows a significant difference after grouping the samples by size. Large enterprises are relatively best, followed by medium-sized enterprises, and small enterprises rank third. Because the small enterprises have relatively weak performance in terms of “internal processes”, “learning, and growth” dimensions. In addition, the analysis of variance also found that the more developed the economy in the region where the enterprise is located, the better its performance in the “customer” dimension. In terms of evaluating the second-level performance indicators for all effective sample enterprises, the performance of the “internal process”, “customer”, and “learning and growth” dimensions is good. However, the performance of the “financial” dimension is poor, with the highest performance weight. Textile and garment enterprises should fully play the role of digital transformation in the “financial” dimension. From the evaluation results of the third-level performance indicators for all effective sample enterprises, “expansion of products or services”, “reduced number of customer complaints”, and “the frequency of enterprise business and violation risk is reduced” have higher weights. Still, the ranking of performance evaluation values is lower. These third-level performance indicators are specific indicators that textile and garment enterprises should focus on and actively improve in digital transformation.